Home before Hospital: a whole of system re-design project to improve rates of home-based dialysis therapy: Experience and outcomes over 8 years. (20th July 2021) - Tombocon, Omar; Tregaskis, Peter; Reid, Catherine; Chiappetta, Daniella; Fallon, Kethly; Jackson, Susannah; Frawley, Fiona; Peart, Dianne; Weston, Ann; Wong, Kim; Palaster, Leanne; Flanc, Robert; et al.
Abstract: Background: Despite evidence that clinical outcomes for patients treated with peritoneal dialysis (PD) or home haemodialysis are better than for patients treated with conventional satellite or hospital-based haemodialysis, rates of home-based dialysis therapies world-wide remain low. Home-based dialysis care is also cost-effective and indeed the favoured dialysis option for many patients. Methods & Objectives: Using a lean-thinking framework and established change management methodology, a project embracing a system-wide approach at making a change where a 'Home before Hospital' philosophy underpinned all approaches to dialysis care was undertaken. Three multidisciplinary working groups (pathway, outreach and hybrid) were established for re-design and implementation. The primary aim was to improve home-based dialysis therapy prevalence rates from a baseline of 14.8% by ≥2.5%/year to meet a target of 35%, whilst not only maintaining but improving the quality of care provided to patients requiring maintenance dialysis. A 'future' state pathway was developed after review of the 'current' state (Pathway Working Group) and formed the basis on which a nurse-led outreach service (Outreach Working Group) was established. With the support of the multidisciplinary team, the outreach service model focussed on early, consistent, and frequent education, patient support in decision-making, and clinician engagement. Results: A target prevalence of >30% for home-based therapies (mainly achieved with PD) was achieved within 2 years. This prevalence rate reached 35% within 3 years and was maintained at 8 years. In addition, selected patients already on maintenance satellite-based haemodialysis (Hybrid Working Group) were educated to achieve high levels of proficiencies in self-care. Conclusion: Having the system-wide approach to a Quality Improvement Process and using established principles and change management processes, the successful implementation of a new sustainable model of care focussed on home-based dialysis therapy was achieved. A key feature of the model (through outreach) was early nurse-led education and support of patients in decision-making and ongoing support through multidisciplinary care.